Teachers’ Beliefs and Decisions Regarding Artificial Intelligence Use in Education - Azis, Muhammad Abdul; Numan, Muhammad (CV. Akademi Merdeka, 2026)
The increasing integration of artificial intelligence (AI) into educational settings has raised important pedagogical and ethical questions, particularly regarding how teachers understand and decide to use AI in their instructional practices. This qualitative study explores teachers’ beliefs about AI use in education and examines how these beliefs shape their instructional decisions. Drawing on semi-structured interviews and thematic analysis, the study reveals that teachers hold nuanced and evaluative beliefs about AI, viewing it as a supportive pedagogical tool while expressing concerns about overreliance, learning quality, and professional responsibility. Rather than adopting AI uncritically, teachers exercise agency through selective integration and pedagogical regulation of AI use, particularly in relation to assessment and student accountability. Teachers’ decisions are shown to be context-sensitive and grounded in humanistic values that emphasize ethical judgment and meaningful teacher–student interaction. The findings suggest that AI use in education is best understood as a belief-driven and value-laden practice rather than a purely technical innovation. This study contributes to educational and humanities-oriented discussions by foregrounding teachers’ professional judgment in shaping responsible and pedagogically sound AI integration.